Identification of Work Accident Hazards Using The JSA Method In the Weaving Section At Pt X - Mulyaningsih, Tri; Ristiawati, Ristiawati; Fitriyani, Nur Lu'lu; Maulana, Jaya (Pena Medika Jurnal Kesehatan, 2024)
Work accidents are incidents related to work and the company. Work accidents occur due to uncontrolled events caused by several factors. According to data from the International Labor Organization (ILO), almost every day people die due to work accidents and work-related diseases at a rate of 2,78 million every year. The preliminary study that has been carried out shows that work accidents occurred in the weaving production section of PT X. The research aims to identify hazards using the Job Safety Analysis (JSA) method. This research uses descriptive research using observational descriptive methods. The sampling technique in this research was purposive, with as many as 4 respondents. This research instrument uses an interview guide and Job Safety Analysis (JSA) table which is analyzed using univariate analysis. The results of this research show that several stages of work in the weaving section have dangers such as being pinched, hammered, cut, hit by a beam, falling or slipping, and electrical short circuits which cause minor injuries, cuts leg fractures, bruises, aches, headaches and fires, machine